Hubungan Antara Stres Kerja Dengan Kelelahan Kerja Pada Perawat Rumah Sakit Di Indonesia - Arja Adi Jaya Pohan; Susilawati Susilawati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Introduction: Work stress in nurses is one of the problems in human resource management in hospitals. Nurses in hospitals are one of the potential resources that have a dangerous risk of burnout in workers. One of the triggering factors for work burnout in workers is work stress experienced by hospital workers. Research objectives: The purpose of this study was to analyze the relationship between work stress and job burnout in hospital nurses in various regions in Indonesia. Research Method: The research method used is the literature review study method by reviewing previous research that is relevant to the topic discussed as a study accessed on the Google Scholar database. Research Results: The results of the research conducted were that there was a significant relationship between work stress and job burnout in hospital nurses in various regions of Indonesia. The conclusion of this study is that work fatigue is influenced by work stress.